Representing public service and post-militariness in Bodyguard (BBC, 2018). Issue 2 (3rd April 2022) - Parry, Katy
ABSTRACT: The opening episodes of BBC1ʹs Bodyguard (2018) broke records for a drama debut, the highest launch figure for any new drama across all channels in the United Kingdom since 2006. This article examines the hit series with a particular focus on notions of public service and post-military identity. The paper explores how the drama conveys 'public service' in the UK context at this specific historic moment, adding to writer Jed Mercurio's oeuvre of dramas that explore the professional ethics of public servants. More specifically, I argue that the analytical lens of 'post-militariness' offers a nuanced way to better understand the complex cultural and political work of the traumatized war veteran from the 9/11 wars, as portrayed in popular media culture. Bodyguard is only one of many dramas representing contemporary war veterans who are often depicted as struggling to transition to civilian life. 'Post-militariness' accounts for both the persistence of military identity as a source of pride and as a source for feelings of betrayal.